The influence of solvents on the appearance of the absorption bands of the polystyrene films deposited from solutions on metal mirrors - Șerban, Sorina Gabriela; Strugariu, Laura Maria; Jitian, Simion (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Infrared reflection-absorption spectra (IRRAS) at the near-normal incidence of polystyrene films from benzene, toluene, and chloroform solutions were analyzed in this paper. The appearance of the spectrum can be affected so that false conclusions can be drawn about the positions and the shape of the absorption bands. The knowledge of these influences of residual solvents in the polymer film is important for the correct interpretation of the reflection-absorption spectra. Unlike other approaches, a single reflection at a 20° incidence angle was used. A new drop-carting technique was used for the deposition of polymer film solutions on metal mirrors. Reflection-absorption spectra at a near-normal incidence angle were obtained using a dispersive infrared spectrometer.
Optica Applicata, Vol. 53, 2023, nr 1, s. 5-19
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; IRRAS; polystyrene; transflection; residual solvent